Pemanfaatan Media Sosial Instagram Sebagai Media Promosi Aneka Dodolan Kauman Di Kota Blitar - Andien Putri Amalia; Siti Ning Farida (Jurnal Pengabdian Kepada Masyarakat, 2023)
The existence of world developments as well as digital transformation has created a “Crisis” situation for every brand and business owner in Indonesia. Because the average businessman is unable to adapt to technology. The increasing number of Instagram users has led to the emergence of Instagram accounts to act as advertising and media channels. One of them is the Instagram social media account @andalan.blitar. Therefore, the purpose of this community service activity is to help digital marketing for UMKM in the Kauman area through Instagram social media. The research method used in this study is a descriptive method which collects data using existing facts. The result of this service activity is that followers have an interest in culinary products that are promoted on the Instagram social media account @andalan.blitar by giving likes, comments, and visiting the UMKM.